Incremental Updates for Efficient Bidirectional Transformations - Wang, M; Gibbons, J; Wu, N (Association for Computing Machinery, 2011)
A bidirectional transformation is a pair of mappings between source and view data objects, one in each direction. When the view is modified, the source is updated accordingly. The key to handling large data objects that are subject to relatively small modifications is to process the updates incrementally. Incrementality has been explored in the semi-structured settings of relational databases and graph transformations; this flexibility in structure makes it relatively easy to divide the data into separate parts that can be transformed and updated independently. The same is not true if the data is to be encoded with more general-purpose algebraic datatypes, with transformations defined as functions: dividing data into welltyped separate parts is tricky, and recursions typically create interdependencies. In this paper, we study transformations that support incremental updates, and devise a constructive process to achieve this incrementality. Copyright 2011 ACM.